2017
DOI: 10.5455/ajvs.276325
|View full text |Cite
|
Sign up to set email alerts
|

Behavior, Fear Response, Performance and Immune Response of Broiler Chicks Fed Graded Levels of Anise Seed as Alternative to Antibiotics

Abstract: Key words:Anise, seed, antibiotic, behavior, performance, stress, fear, immune response.A total of two hundred twenty five day-old Cobb broiler chicks were distributed into five groups (15 birds/ group, three replicates for each treatment). The dietary treatments were designed to fed the chicks of basal diet without supplementation (control), basal diet supplemented with 0.5, 0.75 and 1gm/kg anise seed, and basal diet supplemented with 10g/kg zinc bacitracin (anti-biotic group). Behavioral observation was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…Yazdi et al (2014) reported that there was no significant effect on spleen percentage when feeding chicks with diets containing anise seeds (1, 5 and 10 gm/kg) compared to control at age 6 weeks. On the other hand, the obtained results are in disagreement with Ramadan (2017) who reported that improved bursa percentage was observed in broiler chickens (Cobb) fed diets containing anise seeds (0.5, 0.75 and 1 gm/kg) compared to the control at age 42 days of age. Yazdi et al (2014) found that improved bursa percentage was observed in broiler chickens (Ross 308) fed diets containing anise seeds (1, 5 and 10 gm/kg) compared to the control at 6 weeks of age.…”
Section: Lymphoid Organscontrasting
confidence: 99%
See 2 more Smart Citations
“…Yazdi et al (2014) reported that there was no significant effect on spleen percentage when feeding chicks with diets containing anise seeds (1, 5 and 10 gm/kg) compared to control at age 6 weeks. On the other hand, the obtained results are in disagreement with Ramadan (2017) who reported that improved bursa percentage was observed in broiler chickens (Cobb) fed diets containing anise seeds (0.5, 0.75 and 1 gm/kg) compared to the control at age 42 days of age. Yazdi et al (2014) found that improved bursa percentage was observed in broiler chickens (Ross 308) fed diets containing anise seeds (1, 5 and 10 gm/kg) compared to the control at 6 weeks of age.…”
Section: Lymphoid Organscontrasting
confidence: 99%
“…Our results are in agreement with Ramadan (2017) who found that no significant (P>0.05) effects on spleen percentage when feeding chicks with diets containing anise seeds (0.5, 0.75 and 1 gm/kg) compared to control one at age 42 days of age. Yazdi et al (2014) reported that there was no significant effect on spleen percentage when feeding chicks with diets containing anise seeds (1, 5 and 10 gm/kg) compared to control at age 6 weeks.…”
Section: Lymphoid Organssupporting
confidence: 93%
See 1 more Smart Citation
“…Mohammed (2019) found that an improved body weight and body weight gain were observed in of broiler chickens fed diets containing anise seeds (0.3%,0.6%,0.9%) compared to the control as well as an improved dressing percentage % was observed compared to the control . Moreover body weight gain broiler chickens fed diets containing anise seeds (0.5,0.75, 1 gm/kg) compared to the control besides, improved carcass %was abs observed in 6 week old Cobb broiler chickens compared to the control (Ramadan 2017).…”
Section: Introductionmentioning
confidence: 86%
“…Our finding are in the same line with Mohammed, (2019) who reported that there was no significant effect on wings %, liver%, heart% ,gizzard % when feeding chicks with diets containing anise seeds (0.3%, 0.6%, 0.9%) compared to control diet at age of 42 day. Ramadan (2017) reported that there was no significant effect on liver%, heart %,gizzard % when feeding chicks with diets containing anise seeds (0.5, 0.75, 1gm/kg) compared to control.…”
Section: Carcass Criteriamentioning
confidence: 98%